Evaluation of Diversity Programs in Higher Education Training Contexts in Spain - David Pérez-Jorge; Eva Ariño-Mateo; Ana Isabel González-Contreras; María del Carmen Rodríguez-Jiménez (MDPI AG, 2021)
Measures adopted by educational systems to improve and adapt the educational response of pupils with disability or diversity conditions arising from their personal and social conditions, have enabled them to gain tenure throughout the various stages of education. Educational institutions have been progressively adapting and responding to the educational needs of students who start university, and this fact highlights the lack of inclusive culture in university institutions. The lack of training of university teachers in the educational response to the needs of students with disabilities is evidenced by the high dropout rates of this group and in successive complaints of teachers who do not have the skills or tools to cope with this situation successfully. The review of a set of 75 programs developed by different Spanish universities to meet the needs of these students shows an insufficient institutional and administrative response while reflecting the lack of unity of jointly developed criteria.